The Approach Of Shihab Al-Din Al-Khafaji In His Intakes On Ibn Hisham Al-Ansari In His Book Jokes On Mughni Al-Labib/ منهج شهاب الدين الخفاجي في مآخذه على ابن هشام الأنصاري في كتابه نكت على مغني اللبيب - Al Tamimi, Zakaria (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research dealt with the approach of Shihab al-Din al-Khafaji in his intakes on Ibn Hisham al-Ansari in his book Comments on Mughni al-Labib. He began with an introduction in which he mentioned the importance of Mughni’s book, the significance of the joke book, and the reasons for choosing this topic, and that he had never studied other than the study of the investigator of the book of brief jokes. The research included an introduction and a preface in which he talked about Ibn Hisham, his book Al-Mughni and Shihab Al-Khafaji, and his book Jokes in two sections. The first section was devoted to his diligence and grammatical doctrine and made in two requirements: the first for his efforts and diligence, and the other for his grammatical doctrine. The second section was devoted to evaluating those intakes And made two requirements: the first: for the reasons of the drawbacks, and the other: for the grammatical assets that relied on them in the drawbacks, and concluded the research with a conclusion in which the most prominent results were included. The study used both a descriptive approach and an analytical approach. The research reached results, including that many of the books of Al-Khafaji, may God have mercy on him, are still in manuscript, and that he was free in his choices not affiliated with others, and in many matters of disagreement tended to the Basrians, and agreed with them, and that he did not explain everything that came in Al-Mughni’s text.